indonesia - Dedi Saputra; Maya Panorama; Rinol Sumantri (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
This study was conducted to determine the effect of zakat, infaq, alms (ZIS) and unemployment on economic growth in Indonesia for the period 2012-2021. The type of research used in this research is quantitative research, secondary data taken from access to reports published by the Central Statistics Agency and the National Amil Zakat Agency. By using the method of multiple linear regression analysis processed with the help of eviws 8.0. The results showed that zakat, infaq and alms funds had a positive effect on economic growth while unemployment had no significant effect on economic growth. ZIS funds are able to increase economic growth, indicating that the more effective and efficient the management of ZIS funds at the National Amil Zakat Agency for 2012-2021.